O papel coesivo das conjuções na produção de textos escritos por aprendizes de inglês como língua estrangeira - Barros, Frederico Henrique Rodrigues (2008)
Most EFL students fail to elaborate an objective discourse and express themselves in a cohesive, clear and understandable way. We assume that part of the problem resides in their difficulty to use linking words to join simple and complex sentences. For this reason, we analyzed the role of conjunctions in written texts and how the EFL books deal with them. This research has been done with the participation of 27 EFL students who study at three different private English schools in the state of Pernambuco. As a result of this work, we conclude that there is a sort of limitation on the use of the conjunctions (linking words) in written texts produced by Brazilian EFL students. As a result of this research, we conclude that the use of conjunctions by the EFL students at these three schools is limited to: and but so because . This research work has been based on Text Linguistics, as well as the chart of conjunctions by Halliday and Hasan (1982). It s hoped that this work may call teacher and researchers´ attention to the importance of the cohesive ties in the teaching and learning of the English language